2022
DOI: 10.1088/1361-665x/ac78ad
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling and validation of a soft array of spatially coupled dielectric elastomer transducers

Abstract: Dielectric elastomer (DE) transducers are suitable candidates for the development of compliant mechatronic devices, such as wearable smart skins and soft robots. If many independently-controllable DEs are closely arranged in an array-like configuration, sharing a common elastomer membrane, novel types of cooperative and soft actuator/sensor systems can be obtained. The common elastic substrate, however, introduces strong electro-mechanical coupling effects among neighborg DEs, which highly influence the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…The Neo-Hookean parameter is selected as C 10 = 0.18 MPa according to existing identification procedures based on Wacker Elastosil 2030 material, 23 while its bulk modulus is chosen according to commonly used values for the family of silicone rubbers as K c = 1.5 GPa. 24 By then choosing a sufficiently small value of compressive stretch along the 3rd dimension equal to λ 3 = 0.99, corresponding to a compressive strain ε 3 = λ 3 − 1 = −0.01, the appropriate value voltage value V b is determined with equation (7).…”
Section: In-plane Dea Simulation Resultsmentioning
confidence: 99%
“…The Neo-Hookean parameter is selected as C 10 = 0.18 MPa according to existing identification procedures based on Wacker Elastosil 2030 material, 23 while its bulk modulus is chosen according to commonly used values for the family of silicone rubbers as K c = 1.5 GPa. 24 By then choosing a sufficiently small value of compressive stretch along the 3rd dimension equal to λ 3 = 0.99, corresponding to a compressive strain ε 3 = λ 3 − 1 = −0.01, the appropriate value voltage value V b is determined with equation (7).…”
Section: In-plane Dea Simulation Resultsmentioning
confidence: 99%
“…In our previous research 31 , we observed that single DEA elements, when placed onto the same elastomer membrane, exhibit a strong mechanical interaction with their neighboring actuators. This interaction manifests itself as variations in the mechanical actuation (Figure 3(a)) and sensing curves (Figure 3(b)) of individual DE elements during electrical activation of nearby units.…”
Section: Electro-mechanical Cross-couplingmentioning
confidence: 92%
“…This, in turn, results into high electric fields which are close to the breakdown strength of the material [79,80], negatively affecting the lifetime of the device. In addition, the strong nonlinearities of the material, in combination with the large deformations, makes their accurate modeling and control a highly challenging task [81,82].…”
Section: Dielectric Elastomer Actuators Configurationsmentioning
confidence: 99%
“…By means of model-based optimization, it was possible to optimize the design of the biasing domes and, in turn, achieve a fully polymeric DEA capable of a stroke on the order of 3 mm for an actuator with a radius of 20 mm [109], see Figure 7b. Current research studies focus on the characterization [127] and modeling [82] of the electro-mechanical coupling effects occurring when many of those elements are placed onto a common elastic substrate in an array configuration (cf. Figure 7c), as well as on the development of laser-structuring electrode techniques for enabling local activation of the DEAs [71].…”
Section: One-dimensional Arraysmentioning
confidence: 99%